2012
DOI: 10.1111/j.1365-294x.2012.05728.x
|View full text |Cite
|
Sign up to set email alerts
|

Influences of past climatic changes on historical population structure and demography of a cosmopolitan marine predator, the common dolphin (genus Delphinus)

Abstract: Climatic oscillations during the Pleistocene have greatly influenced the distribution and connectivity of many organisms, leading to extinctions but also generating biodiversity. While the effects of such changes have been extensively studied in the terrestrial environment, studies focusing on the marine realm are still scarce. Here we used sequence data from one mitochondrial and five nuclear loci to assess the potential influence of Pleistocene climatic changes on the phylogeography and demographic history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 86 publications
(99 reference statements)
7
60
0
Order By: Relevance
“…If the mutation rate was an order of Habitat release and incipient speciation I Segura-García et al magnitude slower, the time of divergence would be an order of magnitude older. A previous study used a rate of 9.86 × 10 − 9 for the cytb mtDNA locus to conclude that divergence between sbENP and lbENP took place during the Pleistocene (Amaral et al, 2012). In a comparison between control region and cytb mutation rates in cetaceans, Alter and Palumbi (2009) suggested that the control region evolved 4-5 times faster than cytb.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…If the mutation rate was an order of Habitat release and incipient speciation I Segura-García et al magnitude slower, the time of divergence would be an order of magnitude older. A previous study used a rate of 9.86 × 10 − 9 for the cytb mtDNA locus to conclude that divergence between sbENP and lbENP took place during the Pleistocene (Amaral et al, 2012). In a comparison between control region and cytb mutation rates in cetaceans, Alter and Palumbi (2009) suggested that the control region evolved 4-5 times faster than cytb.…”
Section: Discussionmentioning
confidence: 99%
“…A third morphotype with an even longer rostrum and greater number of teeth was identified in the Indian Ocean and off China, and was nominally identified as a subspecies of D. capensis, D. capensis tropicalis (Jefferson and van Waerebeek, 2002). This putative subspecies is genetically differentiated from the two proposed species (Amaral et al, 2012).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In some cases there is a correlation between population structure and apparent habitat boundaries, as for the bottlenose dolphin (Tursiops truncatus) populations in European waters (Natoli et al, 2005) or with resource specializations as for the killer whale (Orcinus orca) populations in the North Pacific (Hoelzel et al, 2007). Environmental cycles releasing habitat or opening/closing dispersal corridors may also influence the evolution of population structure in these species (Amaral et al, 2012;Moura et al, 2013). For killer whales, some well-studied populations show strong resource specializations based on consistent prey choice (ecotypes) within stable, matrifocal social groups (pods), together with genetic and phenotypic differentiation (Hoelzel et al, 1998;Pitman and Ensor, 2003;Hoelzel et al, 2007;Morin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%